Mycotoxins - the experience and expertise of Micoteca da Universidade do Minho - Paterson, R. R. M. (2003)
A review is made of the work on mycotoxins of current researchers at Microteca da Universidade do Minho. Existing standard methods of screening for total secondary mycotoxins are recommended. The effect of preservation on detection is discussed. Ochratoxin A (OTA) and patulin were detected from fungi from grapes. The influences of vineyard region are discussed. Aspergillus biodegradation products of OTA were OTcx. and other compounds. The same fungus strain produced and degraded OTA. Removal of OTA from liquid to solid occurred during in vitro studies on OTA-spiked and pulped grapes. The novel original reports of (a) metabolites detected from dried herbarium samples, (b) the isoepoxydon dehydrogenase gene probe for the patulin metabolic pathway, (c) patulin from Penicillium brevianamide, (d) bioactivity of brevianamides against insects, (e) indications that 2-deoxyglucose increases patulin production, and (f) mycotoxin production in water are referred to. Priorities for culture collections are suggested.